Upaya Mencapai Smart Economy untuk Mengembangkan Perekonomian di Kota Semarang - Aditya, Dwi Hilda; Ashari, Putra Anas (Jurnal Riptek, 2023)
Smart City is a governance that utilizes information and communication technology in all its fields, so that it will facilitate public access and mobility. One dimension in the smart city concept is the smart economy which focuses on the governance of the city's economic growth.Â  This study aims to determine the efforts made by the Semarang City Government in order to achieve Smart Economy to develop the economy of the people in Semarang City. This research is qualitative research with a descriptive approach. Research data was obtained from literature studies analyzed with a content analysis approach. The results showed that the Semarang City government has pursued various programs to be able to achieve a smart economy in the Semarang Smart City system. These efforts include attracting investors through business meetings, strengthening the workforce, increasing home production, improving farmers' welfare, and revitalizing traditional markets. Investor networking efforts are carried out to increase investment in Semarang City, in order to open up the widest possible job opportunities. Strengthening the workforce is carried out to improve the quality of human resources in Semarang City to be able to compete in the job market, one of which is through the Great Gate movement to alleviate poverty and job training in BLK. In an effort to increase home production, the Semarang City Government assists SMEs to be able to do business through e-commerce and through business partners, especially at souvenir centers. In an effort to improve the welfare of farmers, the Semarang City government launched the Farmer Card to make it easier for farmers to get subsidized fertilizers and superior seeds, as well as the construction of Jalud to facilitate access and mobility of farmers while cutting expenses to increase farmers' income. Meanwhile, efforts made by the government to improve the effectiveness of traditional markets are carried out with traditional market revitalization programs. This is intended so that, the function of traditional markets can compete with modern markets that are currently very easy to find. These efforts are expected to be able to encourage economic growth while improving the standard of living and quality of life of the people of Semarang City.